Level of awareness towards personal financial planning among young adult in Melaka Tengah / Nur Diyana Yaakop - Yaakop, Nur Diyana (2011)
This research project was conducted to determine the level of awareness towards personal financial planning among young adult in Melaka Tengah. The researcher does literature from the past researchers that are related to this study. The literature review helps to describe, summarize, evaluated, clarify, and/or integrate the content of primary report. Nowadays, money management or personal financial planning skill is a vital element in disciplining individual to achieve a quality and balance life. Federation of Malaysian Consumers Associations (FoMCA) president claimed that more than 80,000 Malaysians were declared bankrupt between 2005 and 2010 and these shows young adult in Malaysia generally cannot manage their personal finances. So, the researcher wants to determine the relationships between factors that relates to these issues with the level of awareness. Furthermore, the data methodology then helps the researcher to interpret the data from questionnaire that been distributed to convenient respondent. The method use is relialibility statistic (Cronbach’s Alpha), frequencies (demographic statistic), descriptive statistic and hypothesis testing which consist of Pearson correlation matrix. For this study also, we can see that most of young generation among Melaka Tengah young adult are aware and apply personal financial planning in their daily life but it is just the matters on what are the level of awareness and their money management. After several analyses have been done and the conclusion has made from the result, the researcher comes out with recommendations that may help on these studies.